Service Quality and Experience as Determinants of Tourist Revisit and Recommendation Intentions in Nepal: The Mediating Role of Satisfaction - Thapa, Bhim Kumar; Bajracharya, John; Poudel, Ramesh Rasik (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This study explains the structural relationships among service quality, tourist experience, and tourists' satisfaction levels, in turn, with their intention to revisit and recommend the destination. It also examines the mediating role of tourist satisfaction in these relationships, particularly among international tourists visiting Nepal. The study used a quantitative approach and a cross-sectional survey research design, in which the required data were collected from 405 foreign visitors using self-administered, structured questionnaires. The relationships of service quality, tourist experience, tourist satisfaction, and behavioral intentions were analyzed by using PLS-SEM to identify direct and indirect relationships among the study variables. The results indicate that service quality and tourist experience are important determinants of satisfaction. Satisfaction, in turn, positively influences the intention to recommend and revisit the destination. As a mediating effect, the direct influence of tourists' experience on revisit intention was not significant, but its indirect influence via satisfaction was substantial. The analysis establishes the relevance of Planned Behavior and the Expectation-Confirmation theories, while explaining the tourist behaviors. Tourist satisfaction also forms an important mediating factor between perceived service quality, perceived service experience, and behavioral intentions. The key strategies to promote destination loyalty are to deliver high service standards and to create greater experiential value for international tourists. Thus, the strategy that must be given priority by the tourism stakeholders is the process of enhancing the quality of service, memorable moments to boost satisfaction, foster repeated visits, and positive publicity. Finally, this study contributes empirical knowledge regarding the mediating effect of tourist satisfaction in both prominent and emerging tourism destinations. Besides, it has theoretical and practical implications for sustainable tourism transformation and development.